Gambaran Pengetahuan Remaja Putri tentang Personal Hygiene Selama Menstruasi di SMP Negeri 25 Kota Jambi - Hesty Hesty; Nurfitriani Nurfitriani (Universitas Baiturrahim, 2023)
Adolescence is a period of transition from child to adulthood. This period experienced rapid growth and development both physically and mentally. Young women who have mature reproductive organs and hormones in their bodies will experience menstruation. Cleanliness must be considered because it will affect a person's health and psychology, especially during menstruation. The phenomenon that occurs when young women are still found to be lazy to maintain cleanliness during menstruation. The purpose of this study was to describe the knowledge of young women about personal hygiene during menstruation. The research method used was descriptive research with a cross-sectional design using a purposive sampling technique. Data collection using a questionnaire. The research was conducted at SMP Negeri 25 Jambi City. This research was conducted from September 2021 to August 2022. As for the population in the study, all 7th grade students at SMP Negeri 25 Jambi City totaled 90 students. The sample is 47 female students. The results showed that there were 21 girls with good knowledge (44.7%), 24 girls (51.1%) enough, and 2 girls (4.3%) lacking. Respondents have sufficient and good knowledge about personal hygiene during menstruation because aged 12 and 13 years are at the understanding stage, which can be interpreted as an ability to explain correctly about known objects, and can interpret the material correctly. It is suggested that schools through UKS can work together with the health team to provide health education about reproductive health, especially personal hygiene during menstruation and for subsequent researchers to develop further research related to different variables.